A Comparative Study on Two Person Zero Sum Game Problems Through Computer Algebra (Dhaka University Journal of Science, 2017)
This paper improves a game theoretic algorithm and develops its computer oriented program using MATHEMATICA for solving two person zero sum game problems. The algorithm and computer algebra are drawn upon mainly from two sources, namely the papers H. K. Das, Saha and Hasan5; H. K. Das and Hasan6 being able to solve two person zero sum game problems with single payoff elements. We do a comparative study of the current algorithm and computer technique with the papers5, 6. We show that the current technique is better than the papers5, 6 in saving labor and time for solving two person game problems by analyzing a number of numerical examples.Dhaka Univ. J. Sci. 65(1): 1-7, 2017 (January)